Research on sub-terahertz path loss measurement and modeling for 6G integrated sensing and communication - WANG Yang; ZHAO Haisen; LIAO Xi; ZHENG Xiangquan; LI Chuan; CHEN Qianbin (Tongxin xuebao)
To address the inadequacy of traditional path loss models in accurately describing and characterizing sensing channels, the research on sub-terahertz path loss measurement and modeling for 6G integrated sensing and communication was conducted. A sensing channel path loss model incorporating the echo characteristics of indoor materials was introduced based on radar cross-section theory and an angle-distance joint path loss model for sensing channels was constructed. Using a sub-terahertz channel measurement plat-form based on a vector network analyzer, the fading characteristics of sensing channels at different angles and distances were examined. The measurement results indicate that the angle-distance joint path loss model can accurately capture the variation patterns of sensing channel path loss with respect to distance and angular blockage factors.